Identifikasi Sanitasi pada Kawasan Perdagangan di Kelurahan Kandai Kota Kendari - Indira Maharani; Shirly Wunas; Suriana La Tanrang (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2013)
The low of quality of sanitation supporter infrastructure at commerce area of Kelurahan Kandai Kota Kendari becomes cause the low of sanitation at the area. Condition Of Sub-district Commerce Area of Kandai now impressed is lag compared to commercial area has just in part of town south Kendari, lag from the angle of condition of sanitation covering quality of infrastructure relating to sanitation of itself. Purpose of research is identify condition of sanitation at commerce area, with identifying problemss happened at sanitation supporter infrastructure at area. Data analytical method applied is descriptively quantitative and is qualitative, National Standard comparative analysis Indonesia (SNI). Result of analysis condition of sanitation supporter infrastructure that is in general availibility of infrastructure at commerce area of Kelurahan Kandai has made available, but quality and its the quantity has not according to sanitation standard angle blocks at commerce area. Expansion concept proposal of sanitation at commerce area in the form of expansion concept of drainage infrastructure, waste, wash and privy.